Urgensi Revitalisasi Kearifan Lokal di Tengah Ancaman Bencana Alam Indonesia - Pahrudin HM (Unisia, 2011)
In experiencing life, human being cannot be escaped from nature, especially the natural resources. In order to that, our ancestors have given us immeasurable local knowledges, like the forest restrictions; the depth restrictions; and many more, related to the relation of human being experiencedly with nature. Those indigenous knowledges intended by our ancestors to keeping continuity, preservation and concervation of natural resources that very necessary for human being and life. This article discusses about the importance of the Indonesian communities' local knowledges to keeping concervation and preservation of natural resources, like forest; water; river; and farm. Revitalize of local knowledges are significantly in threat of natural disasters at many Indonesian territories, from Aceh in west to Papua in east, in modern living of human, local knowledges still can be use with refer to it benefits and effects for human life and concervation of natural resources.Keyword: revitalize, natural disaster, local knowledge, natural resources,